New representation of PV buses in the current injection Newton power flow - Oliveira, C. C. [UNESP]; Bonini Neto, A. [UNESP]; Minussi, C. R. [UNESP]; Alves, D. A. [UNESP]; Castro, C. A. (Elsevier, 2017)
This paper presents a comparative analysis of the influence of PV bus representation on the convergence characteristics of the Newton-Raphson Current Injection method. The methods used for solving the power flow problem are based on current injection equations written in polar coordinates. Several tests are presented to clarify the reasons of non-convergence and to provide a broad and fair comparison and evaluation of the performance of the PV bus representation schemes. Performance analyzes were conducted for 57-, 118- and 300-bus IEEE test systems and for two realistic Brazilian systems of 638 and 787 buses, corresponding to parts of the South-Southeast Brazilian system. Several R/X transmission line ratios and loading conditions were considered. The simulation results show that the proposed PV bus representation improves the convergence characteristics of the method.
Keywords: Current injection power flow; Polar coordinates; Power flow; PV representation